Effectiveness of Disaster Risk Governance and Resilience Building: Linkages, Knowledge, Inclusiveness, and Regulation - Mohamed Behnassi; Himangana Gupta; Nira Ramachandran; Matsa Winniefridah; Gopichandran Ramachandran; Silvana Lakeman; Mohammad Ashfaq (Springer, Cham, 2022)
Almost all countries are experiencing disasters whose frequency and intensity have increased over the last decades due to many natural and anthropogenic factors, including climate change. These disasters are increasingly deadly, costly, uncertain, complex, and occurring over a range of temporal and spatial scales. They are the outcomes of inevitable hazards that affect highly vulnerable areas and populations with low coping capacities and resilience. The capacity to anticipate, mitigate and adapt to disaster risk is currently making a significant difference as to whether or not a natural hazard turns into a disaster. Presently, there is no region immune to the impacts of hazards and a country’s vulnerability to disaster risk is the outcome of several factors, mainly the failure of its related governance system. Therefore, countries imperatively need to invest in disaster-resilience building, especially through the development of appropriate governance arrangements according to international frameworks while considering local context dynamics. Disaster resilience is understood here as the ability to adapt to and recover from hazards, shocks or stresses without compromising long-term prospects for development. This process, in order to be effective, requires the consideration of many issues, which will be investigated throughout this chapter, such as: the governance implications of the linkages between disaster risk reduction, climate change and sustainable development goals; the impacts of knowledge gap, uncertainty and science-decision divide; the dynamics through which stakeholder perceptions, awareness and involvement are shaped; the different relevant approaches to be mainstreamed; and the role of laws, policies, and regulations as critical tools in reducing and preventing disaster risk, thus fostering human security.